Perkembangan Emosional Anak di Taman Kanak-kanak Sani Ashilla Ditinjau Dari Orang Tua Yang Bekerja - Anna Miftah Huljannah; Dadan Suryana (Jurnal Family Education, 2022)
Emotional development is one of the important aspects of development that must be prioritized in learning through parents. This study begins with a problem that is found in the condition of students who have not been able to control their emotions when playing with their peers. This study aims to determine the emotional development of children with parents who work at Sani Ashilla Kindergarten. This type of research is descriptive research using a qualitative approach. To see how the emotional development of children with parents who work at TK Sani Ashilla. This type of research is descriptive research using a qualitative approach. To see how the emotional development of children with parents who work at TK Sani Ashilla. The research subjects were B3 graders at Sani Ashilla Kindergarten. The research informants were classroom teachers, center teachers and school principals. Data collection techniques used interviews with classroom teachers, center teachers and school principals, observation and documentation. using interviews with classroom teachers, center teachers and school principals.The results of this study found that parents can help children's emotional development as children can control their emotions and can also share when playing with peers. And negative child behavior such as being angry when playing and not wanting to share toys with friends can be advised and given direction